How to Pay for Telemedicine: A Comparison of Ten Health Systems - Sarah Raes; Jeroen Trybou; Lieven Annemans (Taylor & Francis Group, 2022)
ABSTRACTTelemedicine has the opportunity to improve clinical effectiveness, health care access, cost-savings, and patient care. However, payment systems may form important obstacles to optimally use telemedicine and enable its opportunities. Little is known about payment systems for telemedicine. Therefore, this research aims to increase knowledge on paying for telemedicine by comparing payment systems for telemedicine and identifying similarities and differences. Based on the countries' official physician fee schedules, listing all reimbursed medical services performed by physicians, a comparative analysis of telemedicine payment systems in ten countries was conducted. Findings show that many countries lacked tele-expertise and telemonitoring payment, with the exception for some specific payments such as for telemonitoring in patients with cardiac implantable electronic devices. Moreover, a wide variety of benefit specifications were implemented in all countries to specify which type of clinician contact should be used (remote versus physical) in which circumstances. Payment parity between video and in-person visits was established only in a few countries. Furthermore, fee-for-service was the dominant payment system, although two countries used a capitation-based or hybrid system. The results imply several potential payment challenges when implementing telemedicine: complex benefit specifications, payment parity discussions, and risk of overconsumption due to the dominant fee-for-service system. These challenges appear to be less present in capitation-based or hybrid systems. However, the latter needs to be further explored to harness the full potential of telemedicine.